Formation of Antibacterial Maillard Reaction Products From D-xylose and L-phenylalanine During Stewing Cooking - Hitomi Hirakawa; Hiroshi Ono; Junko Shinozaki; Kento Koyama; Shigenobu Koseki (Journal of Food Protection)
Maillard reaction products (MRPs) produced by heating D-xylose and L-phenylalanine at 121 °C for 1 h have been reported to inhibit the growth of Bacillus cereus and Clostridium perfringens. This study investigated whether MRPs with antibacterial effects could be formed during the stewing cooking of foods at ambient pressure and inhibit spore-forming bacteria in dishes. MRPs were successfully produced by heating D-xylose and L-phenylalanine in phosphate buffer at ambient pressure (<100 °C), with antibacterial effects increasing with temperature, heating time, and substrate concentration. During stewing, MRPs formed at 95 °C for 1–3 h delayed the growth of B. cereus and C. perfringens to an infection dose (106 CFU/mL) during 25 °C storage. For B. cereus, delays were 9.8, 20.3, and 28.5 h in soup curry and 7.4, 15.3, and 26.1 h in beef bowl. For C. perfringens, 1-hour heating delayed growth by ∼13.6 h, while 2- and 3-hour heating suppressed growth to insufficient levels to calculate the time to reach the infection dose. Sensory evaluation revealed that while MRP production had minimal impact on food appearance, it negatively affected smell. Despite this limitation, the simple method of heating D-xylose and L-phenylalanine during stewing offers a promising approach to control spore-forming bacteria in cooked dishes.